2011
DOI: 10.3109/13682822.2010.500316
|View full text |Cite
|
Sign up to set email alerts
|

Literacy skills in primary school‐aged children with pragmatic language impairment: a comparison with children with specific language impairment

Abstract: The results demonstrate that there is a high level of literacy impairment within CwPLI and CwSLI, providing evidence that individualized literacy skill intervention is important for the long-term academic outcome of these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
4
17
0
3
Order By: Relevance
“…In the present study, the FGR children, regardless of gestational age at delivery, tended to have difficulties in phonological awareness (Table ), likely later reflected in their learning skills. These findings are in line with previous results for this FGR cohort : problems in communication skills may be associated with impaired reading and spelling skills in the FGR children .…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the FGR children, regardless of gestational age at delivery, tended to have difficulties in phonological awareness (Table ), likely later reflected in their learning skills. These findings are in line with previous results for this FGR cohort : problems in communication skills may be associated with impaired reading and spelling skills in the FGR children .…”
Section: Discussionsupporting
confidence: 93%
“…Mnogi istraživa i došli su do zaklju aka da greške u itanju nisu rezultat poreme aja relativno jednostavnog mehanizma koji upravlja fonetsko-grafemskom analizom, ve posledice poreme aja u semanti kim poljima i gramatikim kategorijama 1,5,9,10,11 . itanje naglas nije prosto dekodiranje jednog grafi kog sklopa u odgovaraju e glasove, ve je to prenošenje i primanje zna enja iz teksta.…”
Section: Uvodunclassified
“…Motorni mehanizmi artikulacije imaju presudnu ulogu u demutizacionom procesu, jer obuhvataju sve elemente sukcesivnog nastajanja govornih pokreta, koji dovode do formiranja govora (tzv. govorna kinestezija) 11,12 . U enje govora gluvog deteta ne odvija se prirodnim putem i nije bazirano na istim neuropsihološkim dispozicijama feed-backa koji postoji kod deteta koje uje, niti se stvara u periodu u kome još nije došlo do pre-mijelinizacije nervnih puteva.…”
Section: Uvodunclassified
See 1 more Smart Citation
“…) of children with DLD also have difficulties with reading; and Freed et al . () emphasized the heterogeneity of literacy difficulties for children with DLD. Some studies have indicated a direct role for oral language comprehension (Botting et al .…”
Section: Introductionmentioning
confidence: 99%